Changes in the Immune Phenotype and Gene Expression Profile Driven by a Novel Tuberculosis Nanovaccine: Short and Long-Term Post-immunization - Martínez-Pérez, Amparo; Igea, Ana; Estévez, Olivia; Ferreira, Catarina M.; Torrado, Egídio; Castro, António Gil; Fernández, Carmen; Spetz, Anna-Lena; Adam, Lucille; López González, Moisés; Singh, Mahavir; Reljic, Rajko; et al. (Frontiers in Immunology, 2021)
Deciphering protection mechanisms against Mycobacterium tuberculosis (Mtb) remains a critical challenge for the development of new vaccines and therapies. We analyze the phenotypic and transcriptomic profile in lung of a novel tuberculosis (TB) nanoparticle-based boosting mucosal vaccine Nano-FP1, which combined to BCG priming conferred enhanced protection in mice challenged with low-dose Mtb. We analyzed the vaccine profile and efficacy at short (2 weeks), medium (7 weeks) and long (11 weeks) post-vaccination, and compared it to ineffective Nano-FP2 vaccine. We observed several changes in the mouse lung environment by both nanovaccines, which are lost shortly after boosting. Additional boosting at long-term (14 weeks) recovered partially cell populations and transcriptomic profile, but not enough to enhance protection to infection. An increase in both total and resident memory CD4 and CD8 T cells, but no pro-inflammatory cytokine levels, were correlated with better protection. A unique gene expression pattern with differentially expressed genes revealed potential pathways associated to the immune defense against Mtb. Our findings provide an insight into the critical immune responses that need to be considered when assessing the effectiveness of a novel TB vaccine.